Trematode Infections of Gastropods in Saraburi Province - Dechruksa, Wivitchuta; Sungkal, Manuschanok; Leamkaitun, Siriporn; Saetung , Jareeporn; Pumkwean, Phattrawan; Krailas, Duangduen; Veeravechsukij, Nuanpan; Suwanrat, Saranphat (Burapha Science Journal, 2026)
Background and Objectives : Gastropods are economically important and also play a significant role in medical malacology as intermediate hosts of various trematode parasites. Trematode infections of humans and animals are generally classified into four major groups: liver flukes, lung flukes, intestinal flukes, and blood flukes. Each trematode group is transmitted from the definitive host to freshwater snails that serve as the first intermediate host, where the larval stages multiply asexually to increase the number of trematode larvae within the snail. The cercarial stage released from snails then infect the second intermediate hosts and develop into metacercariae, the infective stage found in second intermediate hosts in aquatic animals such as shrimp, snails, crabs, and fish. These metacercarial stage develop into adult flukes in the definitive host following the consumption of raw or undercooked food, except for blood flukes, whose cercarial stage is infective and can directly penetrate the skin of humans and animals, causing schistosomiasis. Trematode infections are found in many areas of Thailand. Knowledge of the distribution of snails that can serve as intermediate hosts in aquatic habitats can provide important information for assessing the risk and epidemiology of trematode infections. Therefore, this study aimed to investigate trematode infections in gastropods and to identify the species of trematodes infecting gastropods in Saraburi Province, which is one of the provinces where outbreaks of paragonimiasis have previously been reported in Thailand. Methodology : Snail samples were randomly collected from natural water sources at 13 sampling sites in 5 districts (Wang Muang, Muak Lek, Kaeng Khoi, Mueang Saraburi, and Sao Hai) in Saraburi Province, Thailand, in June 2023. Snails were collected by hand picking and scooping method using the counts per unit of time method, with five collectors sampled for 10 minutes at each site. Parasitic infections were examined using the shedding and crushing methods. For the shedding method, snails were placed individually in plastic cups containing dechlorinated water and maintained overnight, after which cercarial emergence was examined under a stereomicroscope. The emerging cercariae were described as the morphology based on living cercariae which unstained or vitally stained with 0.5% neutral red. Measurements in micrometers were taken from 10 specimens fixed with 10% formalin. For the crushing method, snail shells were cracked, and the digestive glands were then examined for larval trematodes under a light microscope to estimate trematode infection rates in the gastropods. Snail species and trematode larvae were identified based on morphological characteristics. Main Results : A total of 970 snails were collected and identified morphologically into 15 species. The species identified were Radix rubiginosa (5), Bithynia siamensis siamensis (187), Rivomarginella morrisoni (1), Mieniplotia scabra (118), Melanoides tuberculata (8), Tarebia granifera (362), Anentome helena (183), Mekongia swainsoni braueri (8), M. s. swainsoni (2), Filopaludina filosa (1), F. sumatrensis polygramma (23), F. martensi martensi (63), Indoplanorbis exustus (6), Gyraulus convexiusculus (1) and Pomacea canaliculata (2). The prevalence of cercarial infection in snails was investigated using the shedding and crushing methods. Fourteen snails were found to be infected with cercarial larvae. A total infection rate of 1.44% (14/970). Infected snails were found in five snail species, with M. scabra exhibiting the highest infection prevalence. Cercariae were morphologically classified into three types and four species: type 1, Xiphidiocercariae (Maritreminoides obstipus and Loxogenoides bicolor); type 2, Cotylomicrocercous cercariae (Coitocaecum anaspidis); and type 3, Parapleurolophocercous cercariae (Acanthotrema tridactyla). However, this study identified several snail species in Saraburi Province that serve as the first intermediate hosts for various trematodes. The data showed that five snail species in the families Thiaridae (M. scabra, T. granifera), Viviparidae (F. s. polygramma, F. m. martensi), and Nassariidae (A. helena) can act as the first intermediate hosts for intestinal flukes, which develop into adult worms in fish, frogs, birds, and humans. Although the overall prevalence of trematode infections is low, the detection of medically important cercarial larvae is useful for assessing the potential risk of trematode infection. Conclusions : These studies were found snails variation species from Saraburi province, Thailand. The snails were identified by shell morphology into 15 species consist of R. rubiginosa, B. s. siamensis, R. morrisoni, M. scabra, M. tuberculata, T. granifera, A. helena, M. s. braueri, M. s. swainsoni, F. filosa, F. s. polygramma, F. m. martensi, I. exustus, G. convexiusculus and P. canaliculata. Trematode infections in freshwater gastropods in Saraburi Province revealed five snail species acting as the first intermediate hosts: A. helena, M. scabra, T. granifera, F. m. martensi, and F. s. polygramma. Four species of intestinal trematode cercariae were identified: M. obstipus, L. bicolor, C. anaspidis, and A. tridactyla. In addition, A. tridactyla infected the highest number of gastropod species. Therefore, identifying cercarial species helps to assess the risk of trematode disease occurrence and to understand their adaptation in intermediate hosts. This information provides guidance for enhancing the effectiveness of trematode disease prevention and control in the country.